Memahami Konsep Sakral dan Profan dalam Agama-Agama - Nurdinah Muhammad (Fakultas Ushuluddin dan Filsafat UIN Ar-raniry Banda Aceh, 2013)
In the religious context of everyday life, sometimes it is difficult to distinguish between something that is pure religion and the ideas or interpretations of religion. Something pure religion, comes from God, the absolute and contain sacred values. The ideas of religion, meaning comes from other than God (Human), temporal, changing, and not sacred (profane). In the realization of aspects, sometimes have difficulty distinguishing the two because of overlap and confusion of meaning occurs between religion and religious thought, whether intentionally or not. Subsequent developments, results sometimes religious thought has turned into a religion itself, so it is considered sacred and sinful for those who are trying, breaking and change it. In this case raises questions among some communities; What religion is part of culture or religion or culture in every culture, religion is the most valuable part of the whole social life